The Uncertain Future of Constitutional Democracy in the Era of Populism: Chile and Beyond - Verdugo, Sergio; Issacharoff, Samuel (University of Miami Law Review, 2023)
Largely missing from the extensive discussions of populism and illiberal democracy is the emerging question of 21st century constitutionalism. Nowadays, it is hard to see relevant constitutional changes without a strong appeal to direct popular political participation. Institutional mechanisms such as referenda, citizens’ assemblies, and constitutional conventions emerge as near universal parts of the canon of every academic and political discussion on how constitutions should be enacted and amended. This article’s aim is to offer a cautionary approach to the way participatory mechanisms can work in constitution-making and to stress the difference between the power to ratify constitutional proposals and the forms of governance that must follow. Constitutions are necessarily the product of political and historical moments. Ours is a time of populist challenge to the restraining institutions of governance. We show how constitution-making processes taking place under existing political contexts can fail not simply despite the existence of participatory mechanisms but in large part because of them. We identify two types of failures. First, the authoritarian failure, which consists of constitution-making processes that lead to authoritarian outcomes or become part of democratic backsliding or abusive processes. Second, the activation failure, by which constitutions are not passed. This failure is likely to take place when reforms attempt to bypass established, functioning institutional actors, whatever their flaws. This article will turn to the recent failure of the Chilean constitutional effort (2022) to focus on the historic roles of non-state organizations, most notably political parties, in stabilizing and legitimizing successful democratic governance. The current trend in constitutional formation, reflecting the ascending populist ethos of our times, is to bypass the representative institutions that do exist in favor of a pact between the state and an ill-defined entity known as the people. The tendency of political power without structural checks and balances to lead to autocracy is reasonably well understood. But Chile, together with other recent examples of failed constitutional processes, highlights the risks of activation failure in democratic settings—i.e., contexts in which representative institutions exist and function, though flawed. We will argue that a relevant condition to prevent the activation failure is to use the constitution-making processes as an opportunity to strengthen the political party system by including the existing parties in the process. Success stories of constitution-making have widely shown the advantages that political compromises among rival actors bring in terms of procedural legitimacy—wide acceptance of the constitution’s content—and substantive legitimacy—the inclination of those processes in promoting politically liberal institutions but little has been said about activation failures lacking those features. This article seeks to fill this gap.
Keywords: 59 Ciencia Política::5906 Sociología política; ODS 16 - Paz, justicia e instituciones sólidas